Ambient Drone and Apocalypse - Demers, Joanna (Current Musicology, 2013)
A good time to listen to Celer’s music is early in the morning, around three o’clock. Any later, and road noise would drown it out. In the album Salvaged Violets, high– and low–pitched tones seep in, barely perceptible even on headphones. They are produced on synthesizers, processors of various sorts, and acoustic instruments, but their timbre is uniformly fragile. There are no abrupt attacks, and decays are always attenuated. These tones are too isolated to congeal into harmony; they merely align with each other momentarily, before washing out with the tide.